Evidence for reticulospinal plasticity underlying motor recovery in Brown-Séquard-plus Syndrome: a case report - Eilfort, Antonia Maria; Rasenack, Maria; Zörner, Björn; Curt, Armin; Filli, Linard (Frontiers in Neurology, 2024)
Brown-Séquard Syndrome (BSS) is a rare neurological condition caused by a unilateral spinal cord injury (SCI). Upon initial ipsilesional hemiplegia, patients with BSS typically show substantial functional recovery over time. Preclinical studies on experimental BSS demonstrated that spontaneous neuroplasticity in descending motor systems is a key mechanism promoting functional recovery. The reticulospinal (RS) system is one of the main descending motor systems showing a remarkably high ability for neuroplastic adaptations after incomplete SCI. In humans, little is known about the contribution of RS plasticity to functional restoration after SCI. Here, we investigated RS motor drive to different muscles in a subject with Brown-Séquard-plus Syndrome (BSPS) five months post-injury using the StartReact paradigm. RS drive was compared between ipsi- and contralesional muscles, and associated with measures of functional recovery. Additionally, corticospinal (CS) drive was investigated using transcranial magnetic stimulation (TMS) in a subset of muscles. The biceps brachii showed a substantial enhancement of RS drive on the ipsi- vs. contralesional side, whereas no signs of CS plasticity were found ipsilesionally. This finding implies that motor recovery of ipsilesional elbow flexion is primarily driven by the RS system. Results were inversed for the ipsilesional tibialis anterior, where RS drive was not augmented, but motor-evoked potentials recovered over six months post-injury, suggesting that CS plasticity contributed to improvements in ankle dorsiflexion. Our findings indicate that the role of RS and CS plasticity in motor recovery differs between muscles, with CS plasticity being essential for the restoration of distal extremity motor function, and RS plasticity being important for the functional recovery of proximal flexor muscles after SCI in humans.